Mental Health Status of Lactating Women Residing in Urban Slums and Rural Areas of South India: A Community-Based Cross-Sectional Study - Chimata Naveen; Srinivas Rao Darimisetty; T. Madhu; Chittooru Chandra Sekhar; Niharika Borugadda; A. Sreedevi; Mandava Harshita; Shaik Arif (Indian Journal of Community Medicine)
Background: The transition to motherhood is often characterized by physical recovery, hormonal fluctuations, sleep deprivation, and the challenges of infant care, all of which can contribute to the vulnerability of mothers to mental health issues. The present study was conducted to estimate the burden of poor mental health status of lactating women in urban slums and rural communities. Materials and Methods: A cross-sectional study was conducted on 220 lactating women residing in urban slums and rural areas of Ananthapuramu district. Data was collected by interview method using a pre-designed, semi-structured questionnaire that included Depression, Anxiety, and Stress Scale (DASS-21) for mental health assessment. Multivariate regression analysis was done to determine the predictors for poor mental health status of lactating women. Results: The overall prevalence of mental health issues in lactating women from rural and urban slums was 23.6% and 27.3%, respectively. Predictors for poor mental health of lactating women from rural backgrounds were primipara, lower segment cesarean section (LSCS) type of delivery, and class III socioeconomic status (SES) women, and for urban slums were nuclear family, breastfeeding for less than eight times per day, class III SES women, and intended pregnancy. Conclusions: Almost one in every fourth of lactating women residing in urban slums and rural areas will suffer from mental health issues. LSCS type of delivery and class IV and V SES have a negative impact on the mental health status of lactating women from rural areas. Nuclear family, breastfeeding less than eight times per day, class IV and V SES, and unintentional pregnancy have negative impacts in urban slums.